Seasonal Waterlogging Variation in the Sylhet City Corporation Area, Bangladesh- an Integrated Geospatial Approach - Ha-mim Ebne Alam (Jurnal Geospasial Indonesia, 2022)
Waterlogging is considered a severe environmental hazard in the Sylhet city corporation (SCC) area of northeast Bangladesh adversely affects the local socio-economic development. The integrated geospatial approach presents a worthy alternative to the conventional mapping of waterlogged surface areas. The remote sensing-based water index technique was used for delineating pre-monsoon and post-monsoon waterlogged areas of SCC in 2020 and 2021. Seasonal deviations of the waterlogging were determined by overlaying the waterlogged sites emanated from the pre-monsoon and post-monsoon periods under the GIS environment. Results show that waterlogged areas for pre-monsoon and post-monsoon seasons in 2020 are 2.25 sq. km and 4.12 sq. km, respectively, whereas 2.22 sq. km and 3.90 sq. km in 2021. Hence, the seasonal variations in waterlogged areas in 2020 and 2021 are 1.87 sq. km and 1.68 sq. km, respectively. This analysis also demonstrates that waterlogging in SCC is utterly driven by the high seasonal variations that mainly depend on the amount of rainfall besides the local flood-prone geologic settings and climate change.